PROBLEMS OF DETERMINING THE SUBJECT OF CRIMINAL - LEGAL PROTECTION OF INTELLECTUAL PROPERTY AND ITS PLACE IN THE LEGAL SYSTEM - Станкевич, Юрій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Establishment of an interconnected, logically defined and clear system of the special part of criminal law and the place in it of criminal offenses in the field of intellectual property, functional importance of legal norms in law enforcement is one of the key tasks of scientific research. Purpose: the purpose of scientific research is to determine the subject of criminal protection of intellectual property rights. Some issues of improvement of the legal regulation of criminal liability for committing criminal offenses in the field of intellectual property are considered in this article. Also the purpose of the scientific article is to analyze the scientific impact of criminal law protection of intellectual property on legal relations for the purpose of the realization of scientific practical potential and to create effective guarantees for the protection of the rights of authors of works. Methods of research: general and special methods are used in this article. The results: according to the results of scientific research identified issues of regulation of criminal protection of intellectual property. Discussion: legislation, scientific positions scientists. Considering the urgency of the issues of criminal-law protection of intellectual property, which in its content and purpose formed as a self-sufficient and separate branch of law, such preconditions were created both from the side of law-makers and in the field of law-enforcement, as: for detailing the signs of objective and subjective parties of the compositions criminal offenses in this area, systematic determination of their qualifying features, providing an effective mechanism for the application of such rules of criminal law in combination with other provisions of the Criminal Code of Ukraine.